Preparing for late adulthood in the “course of educational life”. Millennials’ plans to learn in the old age - Konieczna-Woźniak, Renata (Old Age in the Stream of Life: Reflections on Old Age. Volume 2, 2019)
The paper focuses on the problems regarding the preparation of young people for their adulthood, especially the late one, and the problems with growing intergenerational gap between the Baby Boomers and X Generations and the Millennials (Generation Y). Seeking ways of cooperation and ideas for mutual understanding between the younger and the older is a challenge for both andragologists and gerontologists. Learning throughout life, in accordance with the idea of LLL, might be a good space for such a cooperation. The text describes and analyses the learning plans of young people when they grow old, especially in the field of informal education. The Millennials intend to continue their current education, develop passions and interests, or take up new topics that they have not had time for earlier. The development of their adult life occurs as a result of travelling, reading, sport and recreation activities, etc. Lifelong learning, in addition to fulfilling varied educational needs, also means developmental task in learning about adulthood itself at every stage. It can be considered as a dependent of age.